Variabilidade cerâmica do Sítio Cipó - AL, Xingó - Schuster, Adriana Jussara (2018)
This research deals with the ceramist occupation process of the ancient inhabitants of the Cipó site, located on the banks of the lower course of the São Francisco River, in the municipality of Piranhas, Sertão of Alagoas, Xingó region. We seek to understand the cultural processes occurring during the ceramist occupation of this site and the adjacent region of the lower São Francisco, through the analysis and interpretation of the ceramic utensils which hitherto, have not been classified as a tradition or related to an ethnic group. For the accomplishment of this work we analyzed a collection of over 3 thousand sherds, distributed in 11 archaeological layers, cleaning and surface. First, the technical / typological analysis of the fragments was undertook and the morphological sequence was sketched with the hypothetical reconstitution of the rims. The results showed four distinct moments in the pottery of this site. The passage of the second to the third is the most important since it marks the period of contact between the indigenous and the European colonizer. In general, the ceramics of the Cipó site seems not having suffered a definitive rupture of the way producing ceramics. However, in time it is possible to identify the development of new pot forms as well as new attributes in their confection, always maintaining the forms originally used and the similarity with the other ceramics found in Xingó. Hence, the ceramic variability found in the Cipó site may represent a much wider process. Still, this industry has some particular characteristics regarding its stratigraphic distribution and morphological characteristics, with vessels shape and decoration with clear evidences of Xokó ceramics and pots, which present characteristics very similar to those of storing water manufactured by the Kariri groups.